Regulation of DNA Double Strand Breaks Processing: Focus on Barriers - Marini, Federica; Rawal, Chetan C.; Liberi, Giordano; Pellicioli, Achille (Frontiers in Molecular Biosciences, 2019)
In all the eukaryotic cells, nucleolytic processing (resection) of a double strand DNA break (DSB) is a key step to channel the repair of the lesion towards the homologous recombination, at the expenses of the non-homologous end joining (NHEJ). The coordinated action of several nucleases and helicases generates 3′ single strand (ss) DNA, which is covered by RPA and recombination factors. Molecular details of the process have been first dissected in the model organism Saccharomyces cerevisiae. When DSB ends are occupied by KU, a central component of the NHEJ, the Mre11-Rad50-Xrs2 (MRX) nuclease complex (MRN in human), aided by the associated factors Sae2 (CTIP in human), initiates the resection process, inducing a nick close to the DSB ends. Then, starting from the nick, the nucleases Mre11, Exo1, Dna2, in cooperation with Sgs1 helicase (BLM in human), degrade DNA strand in both the directions, creating the 3′ssDNA filament. Multiple levels of regulation of the break processing ensure faithful DSB repair, preventing chromosome rearrangements and genome instability. Here we review the DSB resection process and its regulation in the context of chromatin. Particularly, we focus on proteins that limit DSB resection, acting as physical barriers toward nucleases and helicases. Moreover, we also take into consideration recent evidence regarding functional interplay between DSB repair and RNA molecules nearby the break site.